Humoral immune response to SARS-CoV-2 in pregnant and nonpregnant women following infectionAJOG Global Reports at a Glance - Marni B. Jacobs, PhD; Holly D. Valentine, MPH; Sierra Adkins; Celestine Magallanes, BS; Sydney C. Morgan, PhD; Lissa M. Pereira, MS; Chandana Tekkatte, MS; Abbas Hakim, BS; Peter De Hoff, PhD; Louise C. Laurent, MD, PhD; Priyadarshini Pantham, PhD (Elsevier, 2023)
BACKGROUND: Immune changes that occur during pregnancy may place pregnant women at an increased risk for severe disease following viral infections like SARS-CoV-2. Whether these immunologic changes modify the immune response to SARS-CoV-2 infection during pregnancy is not well understood. OBJECTIVE: This study aimed to compare the humoral immune response to SARS-CoV-2 infection in pregnant and nonpregnant women. The immune response following vaccination for SARS-CoV-2 was also explored. STUDY DESIGN: In this cohort study, 24 serum samples from 20 patients infected with SARS-CoV-2 during pregnancy were matched by number of days after a positive test with 46 samples from 40 nonpregnant women of reproductive age. Samples from 9 patients who were vaccinated during pregnancy were also examined. Immunoglobulin G and immunoglobulin M levels were measured. Trends in the log antibody levels over time and mean antibody levels were assessed using generalized estimating equations. RESULTS: The median number of days from first positive test to sampling was 6.5 in the pregnant group (range, 3-97) and 6.0 among nonpregnant participants (range, 2-97). No significant differences in demographic or sampling characteristics were noted between the groups. No differences in immunoglobulin G or immunoglobulin M levels over time or mean antibody levels were noted among pregnant and nonpregnant participants following SARS-CoV-2 infection for any of the SARS-CoV-2 antigen targets examined (spike, spike receptor-binding domain, spike N-terminal domain, and nucleocapsid). Participants who were vaccinated during pregnancy had higher immunoglobulin G levels than pregnant patients who tested positive for all SARS-CoV-2 targets except nucleocapsid antibodies (all P<.001) and had lower immunoglobulin M spike (P<.05) and receptor-binding domain (P<.01) antibody levels. CONCLUSION: This study suggests that the humoral response following SARS-CoV-2 infection does not seem to differ between pregnant women and their nonpregnant counterparts. These findings should reassure patients and healthcare providers that pregnant patients seem to mount a nondifferential immune response to SARS-CoV-2.